Nurses Assessment Accuracy And Self Confidence In Performing SALT Triage - Hieronimus Amandus; Rima Rianti; Suratno Suratno; Donni Al Ifhan (University of Muhammadiyah Malang, 2020)
Introduction: The nurses' assessment accuracy and confidence in the handling of mass victims of traffic accidents in the prehospital phase was an important success key of subsequent handling of victims when taken to the hospital, and vice versa if there was an error in providing help could be fatal for victims. The purpose of this study was to determine the comparison of face-to-face and watch video simulations of the assessment accuracy and nurses’ confidence in conducting prehospital disaster triage of victims of land traffic accidents using the SALT Triage model.Research Methods: Quasi experimental research with nonequivalent control group design. The sample size was 32 nurses who were divided into 2 groups, namely the face-to-face simulation group and the watch video SALT Triage simulation group. The samples were taken by non-random sampling with purposive sampling technique. Data analysis used was Paired t test and Independent t-testResults: There was no difference in the average nurses’ assessment accuracy and confidence in the face-to-face group with the group watching the simulation video. Statistical test results obtained p value> α = 0.05Conclusion: The sorting mass victims of the SALT Triage model can teach nurses by providing face-to-face or watching a simulation video about SALT Triage. Both ways were equally good at conveying information